2019
DOI: 10.1101/574855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel, dynein-independent mechanism focuses the endoplasmic reticulum around spindle poles in dividingDrosophilaspermatocytes

Abstract: In dividing animal cells the endoplasmic reticulum (ER) concentrates around the poles of the spindle apparatus by associating with astral microtubules (MTs), and this association is essential for proper ER partitioning to progeny cells. The mechanisms that associate the ER with astral MTs are unknown. Because astral MT minus-ends are anchored by centrosomes at spindle poles, we tested the hypothesis that the MT minus-end motor dynein mediates ER concentration around spindle poles. Live in vivo imaging of Droso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The existence of ER-derived membranes around centrosomes has been known for decades through studies using light microscopy (Bergman et al, 2015; Diaz et al, 2019; Harris, 1975; Karabasheva and Smyth, 2019; Poteryaev et al, 2005; Waterman-Storer et al, 1993), but their configuration and functional importance were unknown. Using vEM methodologies, we show that centrosome-associated membranes in C. elegans form a reticulum, leading us to name it the centriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of ER-derived membranes around centrosomes has been known for decades through studies using light microscopy (Bergman et al, 2015; Diaz et al, 2019; Harris, 1975; Karabasheva and Smyth, 2019; Poteryaev et al, 2005; Waterman-Storer et al, 1993), but their configuration and functional importance were unknown. Using vEM methodologies, we show that centrosome-associated membranes in C. elegans form a reticulum, leading us to name it the centriculum.…”
Section: Discussionmentioning
confidence: 99%
“…What might be the function(s) of the centriculum? It was previously suggested that the accumulation of ER around centrosomes in Drosophila serves to ensure that daughter cells receive adequate amounts of ER (Karabasheva and Smyth, 2019). We think that this is unlikely to be the case in C. elegans given that during mitosis, the ER is distributed throughout the cell and the fraction of the ER around centrosomes is relatively small (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation